POLICY INNOVATION TO IMPROVE THE QUALITY OF SCHOOL-BASED ISLAMIC EDUCATION - Asmuni, Hadiqoh (Jurnal Inovatif Manajemen Pendidikan Islam, 2023)
School Based Management (SBM) is a management approach that gives more autonomy to schools, increases flexibility, and encourages active participation from all members of the school community and community. The aim is to improve the quality of education in accordance with existing policies and regulations. SBM involves granting schools a greater degree of autonomy, increased community and parent participation, promoting democratic and professional school leadership, and encouraging professional teamwork. The quality of education is measured through the overall description and characteristics of internal and external services that demonstrate the ability to satisfy expected or implied needs, including educational inputs, processes, and outputs. SBM policy in improving the quality of education can be applied through a SWOT analysis model starting from output-process-input. This model follows a systems thinking approach with an output-process-input sequence, which is chosen because every school activity, including SWOT analysis, can be carried out according to that sequence.